Introduction to the 32nd International Conference on Logic Programming Special Issue. Issue 5 (14th October 2016) - CARRO, MANUEL; KING, ANDY
Abstract : The main track of the Thirty Second International Conference on Logic Programming (ICLP) took place in New York City, USA, from the 18 th to the 21 st October 2016. It seems fitting to hold a significant, power of two, ICLP in New York because the city has a long and distinguished association with logic programming: XSB was developed at Stony Brook, as was HiLog before that, and SB-Prolog before that. Moreover, Picat was developed at the City University of New York, as was B-Prolog, and other logic programming-based systems, such as Ergo. New York has also been (and is) the cradle of several start-ups based on logic programming.